THE PHYSICAL EDUCATION IN THE SOCIAL RE-INSERTION OF ADOLESCENTS FULFIL SOCIAL EDUCATIONAL PROGRAMS (Fiep Bulletin - online, 2014)
The Main objective of this study was to analyse the Physical Education in the recuperation of teenagers who participate of social-educational programs in Porto Alegre. To accomplish that we aimed to characterize the Centro de Atendimento Sócio-Educativo (Social-Educational Assistance Centre) and the transgressor teenagers; to comprehend the Physical Education in the social education system; the activities that are developed in the centre and their benefits; and to analyse this subject as a social and contributing link in the teenagers social re-insertion. The research methodology was characterized in a qualitative, descriptive and interpretative approach using case study. The chosen instruments to collect that data was participating observation, interview, questionnaire and field research diary. Ten teenagers who participate at Centro de Atendimento Sócio-Educativo, the Recreation Technician and the Education Technician have collaborated to this investigation. The interpretation of the collected data resulted in two great analysis' categories. Each one of these categories has its subcategories. The first of them, “social-educational system contextualization”, has the following subcategories: The Social- Educational Centre and the teenagers. The second category named “the Physical Education in the social-educational system”, had as subcategories: activities, benefits and the physical Education as social link. These categories were analysed and offered an understanding about the social benefits of Physical Education to the teenagers recuperation, as well as the comprehension of the possible forms these teenagers can benefit themselves from the Physical Education practice to the social re-insertion.
Keywords: teenagers; social-educational program; Physical Education